Analisis Pengaruh IPM, Pengangguran dan Kemiskinan Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Provinsi Riau - Chinta Aulia Nonika; Lapeti Sari; Bunga Chintia Utami (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Economic growth is one of the main indicators for measuring the success of regional development; however, disparities still exist among regencies and cities in Riau Province. In several regions, the levels of unemployment and poverty remain relatively high, even though the Human Development Index (HDI) has continued to improve over the years. This condition raises questions about the extent to which human development, unemployment, and poverty affect economic growth in Riau Province. This study aims to analyze the effect of the Human Development Index (HDI), unemployment, and poverty on economic growth at the regency/city level in Riau Province. The research employs a quantitative approach using secondary data in the form of panel data covering the period from 2013 to 2024. The independent variables consist of HDI, unemployment, and poverty, while the dependent variable is economic growth. Data were analyzed using the Random Effect Model (REM) to determine the relationship between variables. The results show that HDI has a positive and significant effect on economic growth at the 5 percent significance level, indicating that improvements in human development can enhance regional economic performance. Poverty also shows a positive and significant effect, suggesting that reducing poverty contributes to accelerating regional economic growth. In contrast, unemployment has a negative and significant effect on economic growth in Riau Province, implying that higher unemployment rates can hinder economic progress in the region